(untitled) (Andamios, Revista de Investigación Social, 2007)
This paper is aimed at doing a contribution to the notion of relevant alternative to the philosophy of science: the hypothesis is that such a notion helps enriching the analysis of the relations between orthodox sciences and the problem of dissidence in sciences. And finally we will examine one case presenting the problem of epistemic dissidence in an extreme form: the case of homeopathy. In this sense, given the limitations of this paper, our interest is proposing some clues for the reconstruction and examination of the concept of relevant alternative by examining the relation between homeopathy and actual medicine.